Fish ecology of the alto madre de dios river basin (Peru): Notes on electrofishing surveys, elevation, palm swamp and headwater fishes - Tobes I.; Ramos-Merchante A.; Araujo-Flores J.; Pino-Del-carpio A.; Ortega H.; Miranda R. (My University, 2021)
Our study analyzes the distribution of fish communities related to the environmental variables of the Alto Madre de Dios River, an Andean-Amazon watershed of southern Peru, between 300 and 2811 m a.s.l. within the Manu Biosphere Reserve. We provide new ecological and diversity data on fishes for these poorly studied rivers and new data for palm swamp habitats. With electric fishing techniques, we collected a total of 1934 fish specimens belonging to 78 species, 42 genera and 15 families. To assess main patterns of diversity we combined SIMPER and ANOSIM with canonical correspondence analysis to obtain an overview of the community structure of fish and their distribution related to aquatic habitats. Our results show an important shift on fish diversity at 700 m a.s.l. separating headwater and middle-lowland communities. Electrofishing was a hindrance due to the depth, flow and low conductivity of the rivers, but also allowed us to capture fish not observed with other techniques. We also compared the use of elevation with slope as an alternative variable for statistical analysis. Our results show that slope offers a solid and equivalent explanation for fish distribution variability, avoids redundance, and instead of giving geographical data offers ecologically solid information. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Air quality; Green infrastructure; Spatiotemporal variation; Systematic transitions; Urban land cover